2019
DOI: 10.1111/ppa.13056
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of genetic structures and aggressiveness of Fusarium pseudograminearum populations from two surveys undertaken in 2008 and 2015 at two sites in the wheat belt of Western Australia

Abstract: Fusarium crown rot (FCR), caused predominantly by Fusarium pseudograminearum (Fp) in Australia, is an important fungal disease of wheat and barley. FCR causes significant yield losses and reduced grain quality worldwide. This study investigated the population dynamics of FCR‐causing F. pseudograminearum isolates from Western Australia (WA), a major wheat‐growing region. Wheat samples were collected from a total of seven different sites in 2008 and 2015. Two sites, Tammin and Karlgarin, with moderate to high F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…In this study, for the first time, we determined the mating types of F. pseudograminearum strains in Henan. Our results revealed that F. pseudograminearum strains have both mating idiomorphs, which is consistent with previous studies indicating that the pathogen segregates for both MAT-1 and MAT-2 [4,6,7,40,41]. Although significant ratio differences were detected for the two mating types, MAT-1 and MAT-2, between individual sampling sites, a well-balanced 1:1 ratio of the F. pseudograminearum population in Henan was found overall.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this study, for the first time, we determined the mating types of F. pseudograminearum strains in Henan. Our results revealed that F. pseudograminearum strains have both mating idiomorphs, which is consistent with previous studies indicating that the pathogen segregates for both MAT-1 and MAT-2 [4,6,7,40,41]. Although significant ratio differences were detected for the two mating types, MAT-1 and MAT-2, between individual sampling sites, a well-balanced 1:1 ratio of the F. pseudograminearum population in Henan was found overall.…”
Section: Discussionsupporting
confidence: 92%
“…Of the 44 samples collected from different field sites in Queensland and New South Wales in 2010, DON concentrations in straw from 26 sites exceeded 1 mg/kg, with a percentage of 59% [17]. Similarly to the situation in the Fusarium graminearum species complex (FGSC), the main pathogen of wheat FHB worldwide, three different trichothecene genotypes were identified in F. pseudograminearum species [6,20,26,27], namely, 3-acetyl DON, 15-acetyl DON, and nivalenol (NIV) types. The different toxicological effects observed among the three trichothecene-producing strains make their identification in a given area important in terms of food/feed safety and disease management.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Three triticale genotypes (Ningadhu, Hawkeye and Berkshire) have been reported as susceptible to F. pseudograminearum (Klein et al 1989;Knight and Sutherland 2017), and low or zero levels of disease have been measured in oat cultivars following inoculation with F. pseudograminearum (Nelson and Burgess 1994;Burgess et al 2001;Percy et al 2012). Further to varietal rankings, research into F. pseudograminearum has included the infection process of the fungus (Burgess et al 1975;Wildermuth and McNamara 1994;Percy et al 2012;Knight and Sutherland 2016), genetic resistance including testing genetic structures, aggressiveness and toxigenicity of F. pseudograminearum populations (Bentley et al 2008;Obanor and Chakraborty 2014;Khudhair et al 2019), and yield loss in barley and bread wheat cultivars (Klein et al 1989;Liu et al 2012;Kirkegaard et al 2004).…”
Section: Introductionmentioning
confidence: 99%